Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/robotics11060143
|View full text |Cite
|
Sign up to set email alerts
|

Gecko-Inspired Adhesive Mechanisms and Adhesives for Robots—A Review

Abstract: Small living organisms such as lizards possess naturally built functional surface textures that enable them to walk or climb on versatile surface topographies. Bio-mimicking the surface characteristics of these geckos has enormous potential to improve the accessibility of modern robotics. Therefore, gecko-inspired adhesives have significant industrial applications, including robotic endoscopy, bio-medical cleaning, medical bandage tapes, rock climbing adhesives, tissue adhesives, etc. As a result, synthetic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 206 publications
(328 reference statements)
0
10
0
Order By: Relevance
“…In order to further stress the lubricant and obtain tribological properties from them, it is observed that researchers prefer to use the 4-ball method or the pin on disk method, together they are more than 50% of the tests reported in the literature, for example Reeves et al [8] and Shafi et al [11] both investigated avocado oil with similar pin on disk equipment, Shafi et al [11] reported abrasive wear traits but primarily scuffing wear, on the other hand Reeves et al [8] reported a wear mechanism very similar to that reported by Shafi et al [11], this tells us that the reproducibility in tribological equipment can be reliable if standard methods of measurement of tribological characteristics are followed. As can be seen in Table 3, important reductions in COF and wear are obtained thanks to the action of NPs with very low concentrations of weight % (less than 1.5%), for example, for canola oil Omrani et al [21] and Sikdar et al [22] achieved important reductions in the coefficient of friction of up to 84% and both report a scuffing type wear using NPs of GNP which coincides with the ball milled shape. Both used a tribotester with rotary sliding motion such as ball on disk and pin on disk.…”
Section: Tribological Testing Of Vegetable Oils and Their Nanolubricantsmentioning
confidence: 91%
See 3 more Smart Citations
“…In order to further stress the lubricant and obtain tribological properties from them, it is observed that researchers prefer to use the 4-ball method or the pin on disk method, together they are more than 50% of the tests reported in the literature, for example Reeves et al [8] and Shafi et al [11] both investigated avocado oil with similar pin on disk equipment, Shafi et al [11] reported abrasive wear traits but primarily scuffing wear, on the other hand Reeves et al [8] reported a wear mechanism very similar to that reported by Shafi et al [11], this tells us that the reproducibility in tribological equipment can be reliable if standard methods of measurement of tribological characteristics are followed. As can be seen in Table 3, important reductions in COF and wear are obtained thanks to the action of NPs with very low concentrations of weight % (less than 1.5%), for example, for canola oil Omrani et al [21] and Sikdar et al [22] achieved important reductions in the coefficient of friction of up to 84% and both report a scuffing type wear using NPs of GNP which coincides with the ball milled shape. Both used a tribotester with rotary sliding motion such as ball on disk and pin on disk.…”
Section: Tribological Testing Of Vegetable Oils and Their Nanolubricantsmentioning
confidence: 91%
“…Table 3 presents various studies found in the literature of vegetable lubricants filled with NP additives and their impact in COF and wear. For canola oil, GNPs and hBN were able to lower COF by 52% and 40%, respectively [22]. NPs of hBN in jatropha oil also reduced wear by 20.28% [26], whereas in olive oil the enhancement in wear was of 13% [17].…”
Section: Tribological Performance Of Vegetable Nanolubricantsmentioning
confidence: 95%
See 2 more Smart Citations
“…More importantly, structural design only on the micro-end layer cannot promote the performance of adhesion stability. Although a great deal of work has been done to improve adaptability by introducing soft foam backing into adhesion-based robotic systems, [11,[37][38][39] it is still difficult to avoid the problem of cracks spreading easily due to continuous interfaces. In this case, even if an ideal contact is established based on the compliance of the soft backing, the low tolerance of the continuous adhesion interface to defects results instable gripping of target objects with complex abrupt contours.…”
Section: Introductionmentioning
confidence: 99%